METTL3 Promotes Osteo/Odontogenic Differentiation of Stem Cells by Inhibiting miR-196b-5p Maturation - Xiao Han; Guoyue Li; Haoqing Yang; Chen Zhang; Yangyang Cao; Ning Wang; Lihua Ge; Zhipeng Fan (Stem Cells International)
Mesenchymal stem cells (MSCs) have been considered a potential method for the regeneration of tooth and maxillofacial bone defects based on the multidirectional differentiation characteristics of MSCs. miRNAs have been found to play a key role in the differentiation of MSCs. However, its effectiveness still needs to be improved, and its internal mechanism is still unclear. In the present study, our data discovered that the knockdown of miR-196b-5p promoted alkaline phosphatase (ALP) activity assay, mineralization in vitro, and expressions of osteo/odontogenic differentiation markers DSPP and OCN and enhanced in vivo osteo/odontogenic differentiation of stem cells of the apical papilla (SCAPs). Mechanistically, the results indicated that METTL3-dependent N6-methyladenosine (m6A) methylation inhibited miR-196b-5p maturation by the microprocessor protein DGCR8. Moreover, miR-196b-5p indirectly negatively regulates METTL3 in SCAPs. Then, METTL3 was found to strengthen the ALP activity assay, mineralization, and expressions of osteo/dentinogenic differentiation markers. Taken together, our findings highlight the critical roles of the METTL3-miR-196b-5p signaling axis in an m6A-dependent manner in osteo/odontogenic differentiation of SCAPs, identifying some potential targets for tooth and maxillofacial bone defects.